PAPILLOMA OF THE NASAL CAVITY AND MAXILLARY SINUS IN A 14-YEAR-OLD PATIENT: A CLINICAL CASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The maxillary sinus can be directly or indirectly affected by various benign pathologies of soft and hard tissues. These include cysts, tumors, and tumor-like lesions. Although these conditions are benign, many of them are locally destructive or invasive. Furthermore, malignant neoplasms and chronic inflammatory conditions, which can be more serious, often present with similar clinical and radiographic signs and symptoms. Therefore, it is important to understand the distinguishing features of these conditions and establish a definitive diagnosis, even when suspecting a benign lesion.